What is Enlightenment? : eighteenth-century answers and twentieth-century questions - Schmidt, James (University of California Press, 1996)
This collection contains the first English translations of a group of important eighteenth-century German essays that address the question, "What is Enlightenment?" The book also includes newly translated and newly written interpretive essays by leading historians and philosophers, which examine the origins of eighteenth-century debate on Enlightenment and explore its significance for the present. In recent years, critics from across the political and philosophical spectrum have condemned the Enlightenment for its complicity with any number of present-day social and cultural maladies. It has ra.
Keywords: Enlightenment.; Siècle des Lumières.; Enlightenment (18th-century western movement); PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- History & Surveys -- General.; PHILOSOPHY -- Political.; Enlightenment; Aufklärung; Begriff; Geschichte; Quelle; Verlichting (cultuurgeschiedenis); Mouvement des Lumières.; 18th century.; academic.; criticism.; culture.; english translations.; enlightenment.; essay anthology.; essay collection.; faith.; freedom of expression.; german essay.; german language.; german philosopher.; german philosophy.; germany.; historian.; historical.; immanuel kant.; johann gottlieb fichte.; michel foucault.; modern world.; moses mendelssohn.; philosopher.; philosophy.; revolution.; scholarly.; translations.; world history.; Electronic books.; History